Role of Postmortem Multislice Computed Tomography Scan in Close Blunt Head Injury - Prijo Sidipratomo; Trijono Karmawan Sukana Prija; Bachtiar Murtala; Agus Purwadianto; Gatot Susilo Lawrence (The Indonesian Biomedical Journal, 2014)
BACKGROUND: Conventional autopsy in Indonesia is not well accepted as it is contrary to religion and culture. New radiological imaging method such as multislice computed tomography (MSCT) scan has potential to be a diagnostic tool in forensic pathology. The purpose of this study is to determine the ability of MSCT scan in finding abnormalities in close blunt head injury compared with autopsy.METHODS: This study used descriptive qualitative method. Postmortem cases in Department of Forensic Medicine and Radiology of Dr. Cipto Mangunkusumo Hospital were selected based on inclusion criteria. Then MSCT scan and autopsy were conducted. MSCT scan and autopsy results were compared and analyzed.RESULTS: There were 491 postmortem cases of blunt head injury. However, only 10 cases fulfilled inclusion criteria. Subarachnoid haemorrhages were identified 100% with MSCT scan and 80% with autopsy. Cerebral oedemas were identified 100% either with MSCT scan and autopsy. Subdural haemorrhages were identified 100% with MSCT scan, while 50% with autopsy. Multiple fractures were identified 80% with MSCT scan, while 40% with auto.CONCLUSION: MSCT scan showed a sensitive detection in finding abnormalities in close blunt head injury. Therefore it could be as an alternative choice of examination in close blunt head injury cases.KEYWORDS: multislice computed tomography scan, postmortem, blunt head injury, autopsy